Soil bacterial and fungal communities show within field heterogeneity that varies by land management and distance metric. (February 2023) - Seaton, Fiona M.; Griffiths, Rob I.; Goodall, Tim; Lebron, Inma; Norton, Lisa R.
Abstract: Increasing interest in the use of microbial metrics to evaluate soil health raises the issue of how fine-scale heterogeneity can affect microbial community measurements. Here we analyse bacterial and fungal communities of over 100 soil samples across 17 pasture farms and evaluate beta diversity at different scales. We find large variation in microbial communities between different points in the same field, and if Aitchison distance is used we find that within-field variation is as high as between-farm variation. However, if Bray-Curtis or Jaccard distance are used this variation is partially explained by differences in soil pH and vegetation and is higher under mob grazing for fungi. Hence, field scale variation in microbial communities can impact the evaluation of soil health. Highlights: Understanding of field-scale variation in microbial communities currently limited. Bacterial and fungal community across wide range of pasture farms analysed. High heterogeneity in microbial community over short spatial scales found. Bray-Curtis and Jaccard distance showed variation by soil pH and pasture management. Aitchison distance showed within-field variation similar to between-farm variation.